A review on the development of a porous carbon-based as modeling materials for electric double layer capacitors - Kriangsak Kraiwattanawong (My University, 2021)
Carbon electrodes are a key factor for electric double layer capacitors (EDLCs). Carbon gels have high porosity with a controllable pore structure by changing synthesis conditions and modifying preparation processing to improve the electrochemical performance of EDLCs. This review summarizes the preparation of carbon gels and their derivatives, the criteria to synthesize high surface area in each process, the development by some carbon forms, and EDLC applications. Porous carbons are also prepared as model materials by concentrating on how pore structure increases electrochemical capacitance, such as electronic and ion resistance, the tortuosity of pore channel, suitable micropore and mesopore sizes, and mesopore size distribution. This review emphasizes the significance of pore structures as the key factor to allow for the design of suitable pore structures that are suitable as the carbon electrode for EDLCs.
Keywords: Carbon fibers; Tortuosity; Electric double-layer capacitor; Supercapacitor Materials and Fabrication